Natural Parasitism Influences Biological Control Strategies Against Both Global Invasive Pests Ceratitis capitata (Diptera: Tephritidae) and Drosophila suzukii (Diptera: Drosophilidae), and the Neotropical-Native Pest Anastrepha fraterculus (Diptera: Tephritidae) - Buonocore Biancheri, María Josefina (2022)
Ceratitis capitata (Wiedemann) and Drosophila suzukii (Matsumura) are two severe invasive pests widespread in all Argentinean fruit-producing regions. Both coexist with the Neotropical pest Anastrepha fraterculus (Wiedemann) in northern Argentina. The northwestern region shelters major soft fruit and Citrus producing and exporting industries, which are heavily affected by these dipterans. Eco-friendly strategies are under assessment in Argentina. This study mainly assessed D. suzukii, C. capitata, and A. fraterculus temporal abundance variations and their natural parasitism levels on a 1.5-ha-patch of feral peach trees within a disturbed secondary subtropical rainforest of northwestern Argentina. Fly puparia were mainly collected from the soil under fallen peach. Sampling was performed over three peach fruiting seasons. The most abundant pest species was C. capitata. Drosophila suzukii was only found in the last collecting period, but outnumbered A. fraterculus. Natural parasitism distinctly affected the temporal abundance of these dipterans: it significantly depressed C. capitata abundance in last sampling weeks, it did not substantially affect D. suzukii abundance, but it increased synchronously with the increase in the A. fraterculus abundance. Parasitism on C. capitata was mostly exerted by a combination of both a cosmopolitan pupal and a native larval parasitoid, while A. fraterculus was mainly parasitized by two indigenous larval parasitoids. Only three resident pupal parasitoids were associated with D. suzukii, of which the cosmopolitan Pachycrepoideus vindemiae Rondani (Hymenoptera: Pteromalidae) was the most significant. Data on the resident parasitoid impact are relevant for designing biocontrol strategies in noncrop habitats.